A Qualitative NVivo-Based Exploration of Weather, Climate, and Seasonal Rainfall Variations and Their Socio-Economic Consequences on Sales Volume and Revenue Among Micro, Small, and Medium Enterprises (MSMEs): A Case Study of Kulit Lumpia Bunga Terate in Kasihan, Bantul, Yogyakarta - Sentosa, Agung Mulya; Setiawan, Zunan; Adilla, Fitroh (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study examines how weather patterns, climate shifts, and seasonal rainfall variations shape the sales volume and revenue stability of micro, small, and medium enterprises (MSMEs), with a focused case on Kulit Lumpia Bunga Terate in Kasihan, Bantul, Yogyakarta. The inquiry departs from the premise that small food-based enterprises operate within fragile ecological and market environments, where fluctuating humidity, temperature, and rainfall subtly influence production quality, consumer traffic, and operational continuity. A qualitative approach was chosen to capture these lived realities in a manner that quantitative measures alone cannot express. Data were collected through in-depth interviews with owners, production workers, and local suppliers, supported by field observations during both dry and rainy periods. All qualitative materials were processed and analyzed using NVivo, allowing systematic coding and thematic patterning. The NVivo outputs highlighted three interlinked thematic domains moisture-sensitive production challenge, where humidity and rainfall affected dough consistency, drying time, and defect rates; consumer flow fluctuations, driven by changes in foot traffic, weather-related mobility, and shifting consumption habits during prolonged rains; and adaptive economic responses, including informal inventory strategies, flexible pricing, and selective product diversification to buffer revenue drops. The synthesis of these themes suggests that the enterprise’s economic resilience is strongly tied to its capacity to anticipate and adapt to environmental variability. The findings underscore that climate-responsive production practices, paired with context-specific marketing adjustments, play a crucial role in sustaining MSME performance amid increasingly unpredictable weather conditions.